1984
DOI: 10.2165/00003088-198409030-00007
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline Dosage Prediction in Elderly Patients from Plasma Concentration at 24 Hours after a Single 100mg Dose

Abstract: Fifteen depressed elderly patients (14 female, 1 male; mean age 85 years) received a single oral dose of amitriptyline. The concentration of amitriptyline plus nortriptyline in a blood sample taken 24 hours later was used to predict by means of a nomogram the amitriptyline dosage required for each patient. Each dose was selected to produce steady-state amitriptyline plus nortriptyline concentrations close to 140 micrograms/L. The daily dosage ranged from 20 to 100mg (mean 62mg). Patients received the individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
1

Year Published

1985
1985
1996
1996

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
(2 reference statements)
2
6
0
1
Order By: Relevance
“…Recently, Dawling et al (1984) have demonstrated that a nomogram can be used in elderly depressed patients to predict the dose of amitriptyline necessary to achieve a selected concentration of amitriptyline plus nortriptyline. From our study (Schulz et aI., 1983b) in subjects wh6 received single oral doses of amitriptyline, the normalised concentrations of amitriptyline at 12, 24 a~d 36 hours after the single oral dose were very dependent on the CLo uncorrected for bodyweight (r = 0.88, 0.93 and 0.85 for the 12-, 24-and 48-hour samples, respectively).…”
Section: Css Prediction Studiesmentioning
confidence: 99%
“…Recently, Dawling et al (1984) have demonstrated that a nomogram can be used in elderly depressed patients to predict the dose of amitriptyline necessary to achieve a selected concentration of amitriptyline plus nortriptyline. From our study (Schulz et aI., 1983b) in subjects wh6 received single oral doses of amitriptyline, the normalised concentrations of amitriptyline at 12, 24 a~d 36 hours after the single oral dose were very dependent on the CLo uncorrected for bodyweight (r = 0.88, 0.93 and 0.85 for the 12-, 24-and 48-hour samples, respectively).…”
Section: Css Prediction Studiesmentioning
confidence: 99%
“…However, this relationship is obviously more complex than one which can be represented by a log-linear equation as the linear least-squares regression correlation coefficients were not significantly improved by logarithmic transformation of the data. In our previous studies with elderly depressed patients a relationship was demonstrated between concentrations of nortriptyline obtained at 24 hours after a single dose and those obtained at steadystate (Dawling et al 1981(Dawling et al , 1984. The relationships were linear and allowed construction of drug dosage nomograms for amitriptyline or nortriptyline therapy.…”
Section: Discussionmentioning
confidence: 84%
“…For this reason we previously investigated the relationship between the metabolism of single and multiple doses of both amitriptyline and nortriptyline in elderly patients; there was a good relationship for each drug between concentrations obtained at 24 hours following a single test dose and those at steady-state. This allowed use of the single-dose concentration for prediction of individual dose requirements to achieve steady-state concentrations within a predetermined range (Dawling et al 1981(Dawling et al , 1984. Other investigators have obtained similar results in younger populations using imipramine and desipramine (Brunswick et al 1979;Potter et al 1980).…”
mentioning
confidence: 81%
“…An early single drug level could therefore be used to predict the dosage needed to produce a therapeutic level. When the authors started their work, this method ofrapid dose adjustment had only been prospectively applied and reported for amitriptyline (Dawling et al, 1984;Levyet al, 1982). Since then, Nelson et al (1987) have published a study for desipramine.…”
Section: Discussionmentioning
confidence: 99%
“…Außerdem erhielten 11 von 19 Patienten seit dem 3. Behandlungstag eine Tagesdosis von 250 mg oder mehr Desipramin; bei 10 dieser Patienten war die Dosierung den jeweiligen Erfordernissen angepaßt.When the authors started their work, this method ofrapid dose adjustment had only been prospectively applied and reported for amitriptyline (Dawling et al, 1984; Levyet al, 1982). Since then, Nelson et al (1987) have published a study for desipramine.…”
unclassified